2012
DOI: 10.1021/es302763x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Microplastic on Fitness and PCB Bioaccumulation by the Lugworm Arenicola marina (L.)

Abstract: It has been speculated that marine microplastics may cause negative effects on benthic marine organisms and increase bioaccumulation of persistent organic pollutants (POPs). Here, we provide the first controlled study of plastic effects on benthic organisms including transfer of POPs. The effects of polystyrene (PS) microplastic on survival, activity, and bodyweight, as well as the transfer of 19 polychlorinated biphenyls (PCBs), were assessed in bioassays with Arenicola marina (L.). PS was pre-equilibrated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
485
4
11

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 879 publications
(543 citation statements)
references
References 49 publications
18
485
4
11
Order By: Relevance
“…Positive correlations between food concentration and consumption rates have been described for a range of marine larvae [39][40][41] , possibly explaining why the number of T. gratilla larvae that ingested microspheres and the number of microspheres ingested per larvae, increased with elevated microsphere concentration. Similarly, a positive relationship between the concentration of microplastic and the amount of microplastics consumed has been observed for adults of the polychaete A. marina 15 .…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Positive correlations between food concentration and consumption rates have been described for a range of marine larvae [39][40][41] , possibly explaining why the number of T. gratilla larvae that ingested microspheres and the number of microspheres ingested per larvae, increased with elevated microsphere concentration. Similarly, a positive relationship between the concentration of microplastic and the amount of microplastics consumed has been observed for adults of the polychaete A. marina 15 .…”
Section: Discussionmentioning
confidence: 56%
“…Similarly, Besseling et al 15 and Ugolini et al 19 found no effect of microplastic ingestion on the survival of the adult polychaete A. marina and amphipod T. saltator. Sublethal effects of ingestion of microplastics were more apparent, manifesting as reduced larval body width.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…[32][33][34][35][36] Hence, when microplastics, because of their minuteness, enter marine food webs at low trophic levels they simultaneously harbour the risk of potentially propagating these toxic substances up the food chain. [37,38] This issue is discussed controversially in recent research and although several studies suggest it being of minor importance from a risk assessment perspective [39,40] microplastics have the potential to transport POPs to human food. [33] In addition, because of their material properties many microplastic particles are buoyant and their durability enables them to travel long distances.…”
Section: Introductionmentioning
confidence: 99%
“…Microplastics can therefore act as carriers for the transport of those contaminants. When ingested by aquatic organisms, contaminants carried by microplastics can be released and induce associated harmful effects (Bakir et al 2014a;Besseling et al 2012;Rochman et al 2013b).…”
Section: Introductionmentioning
confidence: 99%